Recurring Cystitis: How Can We Do Our Best to Help Patients Help Themselves? - Sarah Ben Hadj Messaoud; Elisa Demonchy; Véronique Mondain (Antibiotics, 2022)
Recurrent cystitis (RC) has rarely been studied; its management varies and research on a holistic approach of these patients is scarce. We attempted to characterize patients suffering from RC and investigated their current care pathways, aiming to offer customized and autonomous management. In this paper, we present a descriptive, single-center, cross-sectional study of women presenting with RC at an infectious disease (ID) clinic. A questionnaire was developed and was completed by ID physicians during patient visits. From October 2016 to January 2019, 202 women were included (mean age 59 years). Sexual intercourse, stress and diarrhoea/digestive symptoms were reported as trigger factors by 35%, 34% and 19% of patients, respectively. A majority (54%) were at risk for complications and were those more exposed to inappropriate antibiotic prescriptions. In total, 56% of women suffered from more than 10 episodes/year and 48% suffered from relapses, mainly due to E. coli. Genitourinary syndrome of menopause (GSM) was a frequent complaint (74.5% of women). Fluoroquinolones and 3rd generation cephalosporins were prescribed in 38% and 30% of women, respectively. Most women wished for non-antimicrobial approaches and autonomy. Patients require comprehensive, tailored care in order to benefit from a broader range of treatment options in compliance with recommendations.